Morphological and Pharmacognostical Evaluation of Moringa oleifera Lam. (Moringaceae): A Plant with High Medicinal Value in Tropical and Subtropical Parts of the World - Singh, Monika; Singh, Shilpi; Verma, Digvijay (Pharmacognosy Reviews)
Moringa oleifera Lam. is a very important medicinal plant grown in the Indian subcontinent and it belongs to the family Moringaceae. This is popularly known as drumstick tree and is used as a food delicacy very popularly. This plant is now well known for its various nutritional properties such as rich source of Vitamins (A and C), minerals (Ca, P, K, Fe, Cu, S, Mg) etc. pharmacological properties such as anti-inflammatory, abortifacient, Antioxidant, analgesic, antipyretic, etc. All the parts of the plant are used in one way or the other. There have been no complete records on morphological and pharmacognostical studies of the whole plant. In this research article we have tried to examine the complete morpho-anatomy of the plant Moringa oleifera Lam. Simple pharmacognostic studies including macroscopy, microscopy, biostatistical parameters and powder analysis and fluorescent analysis have been performed. The peculiar features observed were the presence of mucilaginous canals in stem and mature petiole; myrosine in all parts of the plant, stellate and rhomboid crystals, reticulate and spiral thickenings in the xylem vessels. The results can be used for further characterization of the plant.
Keywords: Moringa; Pharmacognosy; Microscopy; Powder microscopy; Standardization